1997
DOI: 10.1046/j.1365-2559.1997.5450786.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for a clonal link between low and high‐grade components in gastric MALT B‐cell lymphoma

Abstract: High-grade MALT lymphomas often contain low-grade tumour components; both cell populations have been shown to express the same immunoglobulin light chain previously. However, the clonal link between the low and high-grade components has not been established at the genetic level. To investigate this link, we have examined low- and high-grade components micro-dissected from tissue sections of four high-grade gastric MALT lymphomas. PCR and sequence analyses were performed to identify clone-specific rearranged im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 28 publications
2
78
0
1
Order By: Relevance
“…Some studies are supportive of a lymphomagenesis of high-grade MALT lymphoma from low-grade MALT lymphoma, eg by showing clonal relationship between low-and high-grade lymphoma cells. 3,4,[43][44][45] It might be hypothesised that MALT lymphocytes undergo a sequence of genetic changes that ultimately lead to high-grade MALT lymphoma. In this case, one would expect to find aberrations of the low-grade tumour to be present in the high-grade tumour cells as well.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies are supportive of a lymphomagenesis of high-grade MALT lymphoma from low-grade MALT lymphoma, eg by showing clonal relationship between low-and high-grade lymphoma cells. 3,4,[43][44][45] It might be hypothesised that MALT lymphocytes undergo a sequence of genetic changes that ultimately lead to high-grade MALT lymphoma. In this case, one would expect to find aberrations of the low-grade tumour to be present in the high-grade tumour cells as well.…”
Section: Discussionmentioning
confidence: 99%
“…They found "unmasked" histologically high-grade disease in all patients [99]. Immunohistochemical studies, as well as PCR of immunoglobulin heavy chain gene rearrangements, demonstrated that the low-and high-grade components derive from the same clone [100].…”
Section: High-grade Gastric Malt Lymphomamentioning
confidence: 99%
“…4 However, the strongest argument for this hypothesis is the demonstration of a clonal relationship between both lymphoma subtypes within the same patient. 5,6 This progression of a low grade MALT lymphoma to a high grade lymphoma has been demonstrated to be associated with the loss of Bcl-2 expression, inactivation of p53 and c-myc rearrangement. [7][8][9][10] It is not likely that all diffuse large B cell lymphomas represent transformed low grade MALT lymphomas, since features of a low grade component are only found in 30% of cases.…”
Section: Introductionmentioning
confidence: 99%